(untitled) (KYAMC Journal, 2021)
Appendicitis has its acute, subacute, recurrent and chronic forms. Appendicitis is commonly predisposed to and precipitated by a single or a combination of multiple discrete factors like obstruction of lumen, ischemia from thromboembolic episodes, infection or idiopathic etc. Typically, it starts as umbilical or peri-umbilical or midline abdominal dull aching pain that soon gets localized in the right iliac region. Movements worsen the pain. Other typical features include nausea, vomiting, anorexia, pyrexia, preference to lie down with or without curling up, chills, constipation, diarrhea, fever, shaking etc. The atypical symptoms of appendicitis include a dull or sharp pain anywhere in the abdomen, back, rectum, painful urination, bloating, flatulence, generalized abdominal tenderness, distension simulating acute intestinal obstruction, enlarging abdominal mass with or without overlying skin erythema, normal bowel movements, normal vital signs and even with no pain, no nausea, no vomiting no pyrexia or no weight loss. These atypical symptoms very often misguide the primary care physicians and the surgeons resulting in failure of diagnosis putting the patients to the risks of life-endangering complications. Diagnosis of appendicitis in absence of typical features are to be made from pre-occupied knowledge and clinical suspicion with or without the help of biochemical and/or imaging studies. Early and timely diagnosis and appropriate treatment are essential to save the life and to reduce the morbidity as well. Appendicitis should be thought in all cases of abdominal pain irrespective of its type and location, as must meningitis be thought in all cases of headaches. KYAMC Journal.2021;12(02): 101-106